Empirical Assessment of Ethnic Identity and Ethnic Attitudes of the Russian Students (Case Study of Humanities Degree Programmes taught at National Research Mordovia State University) - Sergey I. Balyaev; Zhanna G. Garanina; Sergey N. Nikishov; Irina S. Nikishova (National Research Mordova State University, 2024)
Introduction. Currently, there is a tendency of steady decline in the value of ethnic identity in the self-consciousness of young people. The assessment and study of the dynamics of ethnic self-awareness are related to the need for a comprehensive approach to the problem of patriotism development of modern Russian youth. The purpose of this article is to analyze the ethnic self-consciousness and ethnic attitudes among Russian youth enrolled in humanities degree programmes at the National Research Mordovia State University. Materials and Methods. 150 junior students took part in the empirical research. The following methods were used: the 16PF questionnaire by R. Cattell (form C), the "Types of Ethnic Identity" method by G. U. Soldatova and S. V. Ryzhova, the Method for assessing the positivity and uncertainty of ethnic identity by A. N. Tatarko, N. M. Lebedeva, ethnic affiliation questionnaire by G. U. Soldatova, S. V. Ryzhova. The authors used methods of correlation and factor analysis. Results. The study revealed a high level of positive ethnic identity in the majority of Russian students. The greater part of students have an average level of ethnic identity. The results of correlation analysis showed the presence of significant relationships between types of ethnic identity and ethnic attitudes. As a result of factor analysis, five groups of factors reflecting the relationship between types of ethnic identity and personal qualities of students were identified. Discussion and Conclusion. The authorsʼ findings contribute to the study of the problem of ethnic identity and its relationship with ethnic attitudes and personality traits of Russian students. The materials of the article can be useful for specialists in the field of ethnic psychology to study and develop studentsʼ deep understanding of their own ethnic identity.